Resíduo eletrônico : perspectiva ambiental das ações na formação profissional no Instituto Federal de Sergipe - Santos, Luiz Carlos Pereira (2016)
Professional courses can promote educational activities through an interdisciplinary approach in the classroom use of electronic waste as procedures to form subject aware. The Federal Institutes while locus can enhance vocational training articulated with social reality and thus meet the prerogatives of the laws in force regarding solid waste policies. To that end, the goal of this thesis is the observation that the theory must be correlated with the practice in the laboratory, namely, content related to the object of study (electronic waste) in the mid-level technical course of maintenance and computer support in order to verify as teachers and graduates are realizing the electronic waste and its organizational forms in the school environment. The survey was methodologically in the case study, adopting a qualitative and quantitative approach of interpretative nature-reflective. In this sense, the electronic waste, while pedagogical support instrument inserted into the content of the various disciplines of the technical course in Computer maintenance and support functions as a mediator in the teachinglearning process by virtue of its relationship with the problem of electronic waste, enabling the construction of knowledge; demonstration of the use of efficient forms of reuse, recycling and utilisation of this waste. Yes, the evidence presented by the graduates and teachers showed that the practices in electronic waste allowed form subject conscious, critical and reflective on the basis of a broad training in Environmental education is present in this professional context.